Alpha-Asaronol Alleviates Dysmyelination by Enhancing Glutamate Transport Through the Activation of PPARγ-GLT-1 Signaling in Hypoxia-Ischemia Neonatal Rats - Ge, Yuhang; Zhen, Fei; Liu, Ziqi; Feng, Zhaowei; Wang, Gui; Zhang, Chu; Wang, Xingqi; Sun, Ying; Zheng, Xiaohui; Bai, Yajun; Yao, Ruiqin (Frontiers in Pharmacology, 2022)
Preterm white matter injury (PWMI) is the most common form of brain damage in premature infants caused by hypoxia-ischemia (HI), inflammation or excitotoxicity, characterized with oligodendrocyte precursor cells (OPCs) differentiation disorder and dysmyelination. Our previous study has confirmed that alpha-asarone (α-asaronol), a small molecular compound isolated from the Chinese medicinal herb Acorus gramineus by our lab, could alleviate neuronal over-excitation and improve cognitive function of aged rats. In the present study, we investigated the effect and mechanism of α-asaronol on myelination in a PWMI rat modelinduced by HI. Notably, α-asaronol promoted OPCs differentiation and myelination in the corpus callosum of PWMI rats. Meanwhile, the concentration of glutamic acid was significantly decreased and the level of PPARγ and glutamate transporter 1 (GLT-1) was increased by α-asaronol treatment. In vitro, it was also confirmed that α-asaronol increased GLT-1expression and recruitment of PPARγ co-activator PCG-1a in astrocytes under oxygen and glucose deprivation (OGD) condition. PPARγ inhibitor GW9662 significantly reversed the effect of α-asaronol on GLT-1 expression and PCG-1a recruit. Interestingly, the conditional medium from α-asaronol-treated astrocytes decreased the number of OPCs and increased the number of mature oligodendrocytes. These results suggest that α-asaronol can promote OPCs differentiation and relieve dysmyelination by regulating glutamic acid level via astrocyte PPARγ-GLT-1 signal. α-asaronol may be a promising small molecular drug for the treatment of myelin-related diseases.